PENGENALAN DAN PELATIHAN KALIGRAFI JEPANG BAGI SISWA SMU DI JAWA TENGAH - Fadli, Zaki Ainul; Ratna, Maharani; Hastuti, Nur; Widiandari, Arsi; Saraswati, Dewi (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
Japanese Caligraphy – Shodo, is a work of art that expresses the beauty of kanji characters on paper by writing using brushstrokes. The art of calligraphy is popular in Japan from elementary school children to the elderly and already widespread in the world. The tools used during shodo include shitajiki, bunchin, suzuri, sumi, and fude. At the beginning of shodo, one must pay attention to his posture and hand to get good results. It is strongly advised so that the result can be as good as it is written with Japanese brush/fude. There are some various kinds of Japanese shodo, such as kaishou, gyousho, shousho. Usually shodo can be seen in some Japanese traditional events, such as Japanese wedding ceremony, Japanese tea ceremony room, in houses during new year, etc.